Prediction of returns on equity - Lim, Hwee Sin (2009)
There's little argument that returns from investments, is to a large extent, affected by occurrences of future events. Successful investing is, therefore very much dependent on one's ability to predict the future. However, future events often contain surprise elements that are beyond the most sophisticated forecasting tools. Nonetheless, studies on forecastable components in security returns have shown some degree of success particularly over the intermediate to longer-term horizon. Fama and French (1988) in studying the New York Stock Exchange reported that as much as 25 to 40 per cent of stock returns are predictable over a 3 to 5 years time horizon. This represents a radical shift from the previously held view of the efficient market hypothesis (EMH) as predictability implies market inefficiency. Ironically, the efficient market theory was originally attributed to Fama's classic work (1965) which presented strong and voluminous evidence in favour of the random walk hypothesis.